Chronic complications of diabetes: Contemporary classification - Sanjay Kalra; Saptarshi Bhattacharya; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Traditionally, chronic complications of diabetes have been classified as microvascular and macrovascular. As our knowledge and understanding of diabetes develops, we increasingly find that conventional classifications and frameworks are unable to encapsulate the wide spectrum of the syndrome. We propose a seven-angled rubric, to serve as a contemporary taxonomic structure for diabetes complications. This includes not only the vascular consequences, but sapio-metabolic, oculo-metabolic, viscero-metabolic, musculoskeletal and repro-metabolic complications of diabetes as well. This taxonomic structure, presented in tabular and hexagonal form, should prove useful for all students of diabetology Keywords: Chronic disease, complications, diabetes, type 2 diabetes, vascular complications, vessel disease